Malignant Mesothelioma: Cell Survival Pathways and Radiation Therapy - Sayan, Mutlay; James Wallace III, H.; Heimann, Ruth; T. Mossman, Brooke (Current Respiratory Medicine Reviews, 2015)
Malignant mesothelioma is an insidious cancer with a long latency period from the initial exposure to asbestos, the most common causative agent. Patients show minimal response to current treatment options, resulting in a median survival time from diagnosis ranging between 12-18 months. Although recent studies have enhanced our understanding of mesotheliomas, treatment strategies that range from supportive care to radical trimodality therapy have limited efficacy. Aside from being an essential component of trimodality therapy for mesotheliomas, radiation therapy has been also utilized as a prophylaxis for drain-site recurrence and palliation of pain. However, the efficacy of radiation therapy is limited by the development of radiation resistance due to the activation of pro-survival cell signaling pathways. Blocking these important signaling pathways with pharmaceutical inhibitors or other approaches such as RNA interference has considerable potential to enhance the efficacy of radiation therapy in mesothelioma. This brief review focuses on the effects of radiation therapy in mesothelioma and resultant activation of pro-survival signaling pathways.
Keywords: CREB